Inducing Planar Orientation in Side‐Chain Liquid‐Crystalline Polymer Systems via Interfacial Control. Issue 1 (18th January 2016) - Nagano, Shusaku
Abstract: For efficient photoresponses of liquid‐crystal (LC) azobenzene (Az) polymer systems, planar LC orientation of the Az mesogenic group is required because the light irradiation process usually occurs with normal incidence to the film surface. However, LC molecules with a rodlike shape tend to orient perpendicularly to the film surface according to the excluded volume effect theory. This review introduces new approaches for inducing planar orientation in side‐chain LC Az polymer films via interface and surface molecular designs. The planar orientation offers efficient in‐plane photoalignment and photoswitching to hierarchical LC architectures from molecular LC mesogens and LC phases to mesoscopic microphase‐separated structures. These approaches are expected to provide new concepts and possibilities in new LC polymer devices. Abstract : New methods and strategies to control molecular orientation for polymer thin films are proposed in this review. Moreover, they demonstrate the effectiveness and impact of the free surface in thin films on molecular orientation. The film surfaces have not been treated as a major subject to control molecular orientation. New methods were demonstrated for controlling the inner structures (molecular orientation) of polymer films from the surface/interface of thin films.